Heraldo Marelim Vianna na história da avaliação educacional no Brasil - Paschoalin, Pamela Cristina Botiglieri (Universidade Federal de São Carlos, 2019)
Heraldo Marelim Vianna was an influent researcher in the area of educational evaluation in Brazil, knowed as one of the firts to discuss this theme, and with a very important role in the Carlos Chagas Foundation (FCC), an entity of great importance for the studies on educational evaluation. Because it has a wide production on the subject, this research aims to analyze Heraldo Marelim Vianna’s production relating it with the historical route of educational evaluation in Brasil. The research is a documentary study, in which from the survey, reading and analysis of the author's works, together with interviews with FCC researchers who lived with him, it is intended to draw a line of understanding about the scientific production of Heraldo Marelim Vianna regarding the field of evaluation education in Brazil. A selection of the author’s works was made, and its division between two phases (1970s and 1980s and 1990s) and, based on what was discussed, concluded that during the first phase of his production Vianna dedicated himself to the study of educational measures, selection area and vestibular selection. It was a period in which the demand for access to higher education was growing and in which Vianna would have worked about the emerging need to construct selection instruments. Otherwise, in the second phase of its production, Vianna was conceived to focus on the subject of educational evaluation and its role as instrument for reflection and improvement of education. It was a period in which the educational evaluation, although recommended and inserted in schools, was often not used as an object of reflection and guidance of the educational process. We realized, therefore, that the production of Vianna was having its focus changed according to the demands of each context in wich the author was inserted. Thus, it is expected that the research contributes to the area of education, providing an analysis of the production of reference authors for the field of educational evaluation in Brazil, and relating the moments of the trajectory of educational evaluation in the country.
Heraldo Marelim Vianna in the history of educational evaluation in Brazil
Keywords: Avaliação educacional; História da avaliação educacional; Heraldo Marelim Vianna; Educational evaluation; History of educational evaluation; CIENCIAS HUMANAS::EDUCACAO